PORTADA “La Atención Del Personal Médico No Especializado Y Su Incidencia En El Tratamiento A Los Pacientes Diabéticos Que Asisten A La Consulta Del Hospital Sagrado Corazón De Jesús De La Ciudad De Quevedo Durante El Año 2014”. - CEVALLOS GALARZA, Hugo (2014)
Diabetes is a chronic non-communicable disease, preventable is among the seven leading causes of death of the Ecuadorian population, especially the elderly. This research was conducted in order to decrease the morbidity and the presence of complications in diabetic patients, define the catastrophic conditions are those diseases that threaten the lives of those who suffer .The study population was 165 diabetic patients three doctors, two nurse, has been a subject of analysis and processing difficult it must be viewed from the field of public health and from the family and the individual. It should be noted that in our country is based healthcare as a right as stipulated in the constitution of the republic. Our study therefore seeks. Analyze the attention of non-specialist medical staff and their impact on the treatment of diabetic patients and determine the readiness of health workers.